Treating latent tuberculosis infection (LTBI) with isoniazid and rifapentine (3HP) in an inner-city population with psychosocial barriers to treatment adherence: A qualitative descriptive study. - Amber Heyd; Courtney Heffernan; Kate Storey; T Cameron Wild; Richard Long (Public Library of Science (PLoS), 2021)
In Canada, preventive therapy for latent tuberculosis infection (LTBI) has required multiple doses of medication over an extended period of time. Such regimens are associated with poor adherence and completion rates. A shortened treatment regimen of once weekly isoniazid plus rifapentine for 3 months (3HP), is now available, and holds promise in populations facing challenges to treatment adherence. Although many factors impact treatment adherence, a knowledge gap exists in describing these factors in the context of this regimen. We present findings from a qualitative descriptive study, involving semi-structured interviews with unstably housed or homeless individuals in Edmonton and Fort McMurray, Alberta, Canada who were offered directly-observed preventive therapy (DOPT) with 3HP, and their health care providers. Latent content analysis revealed incomplete understandings of LTBI and about the need for preventive therapy. Clients' motivation to be healthy, alongside education, health care outreach, relationships developed in the context of DOPT, ease of treatment regimen, incentives, and collaboration were all described as supporting treatment completion. Competing priorities, difficulty in reaching clients, undesirable aspects of the regimen and difficulties obtaining and initiating 3HP were identified as barriers. Perceptions of stigma related to LTBI and TB were described by clients in addition to feelings of shame related to their diagnosis. Our study provides insight into LTBI and indicates that multiple interacting psychosocial factors influence preventive therapy access, uptake, and adherence. Findings from this study of both client and provider perspectives can be used to inform and address inequities among individuals experiencing homelessness, and ultimately contribute to a diminished reservoir of LTBI.